1994
DOI: 10.1111/j.1939-1676.1994.tb03231.x
|View full text |Cite
|
Sign up to set email alerts
|

0–7–21 Radiation Therapy for the Treatment of Canine Oral Melanoma

Abstract: Eighteen dogs with malignant melanoma of the oral cavity were treated with high-dose per fraction (0-7-21 ) radiation therapy. Eight hundred cGy was administered on days 0,7, and 21 for a total dose of 2,400 cGy in 3 weeks. Of 1 7 dogs evaluated, 9 (53%) had a complete remission and 5 (30%) achieved a partial remission with an overall response rate of 83%. Local failure occurred in 2 of the 9 dogs where a complete response was initially observed. One dog died of intercurrent disease, and one died of metastatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 34 publications
3
69
0
2
Order By: Relevance
“…17 After radiation therapy of 5 dogs with stage I tumors, 3 dogs with tumors of the lip survived or died of unrelated causes, whereas 2 dogs with tumors of the buccal mucosa died of tumor-related disease. 2 Another study of oral malignant melanomas reported median survival after radiation therapy of 86 weeks for tumors ,5 cm 3 , which was significantly longer than that of dogs with larger tumors. 5 Postradiation progression-free survival of dogs with T1 oral melanocytic neoplasms was reported to be 38 months (mean) and 18.8 months (median), which was significantly greater than that of dogs with T2 and T3 tumors.…”
mentioning
confidence: 99%
“…17 After radiation therapy of 5 dogs with stage I tumors, 3 dogs with tumors of the lip survived or died of unrelated causes, whereas 2 dogs with tumors of the buccal mucosa died of tumor-related disease. 2 Another study of oral malignant melanomas reported median survival after radiation therapy of 86 weeks for tumors ,5 cm 3 , which was significantly longer than that of dogs with larger tumors. 5 Postradiation progression-free survival of dogs with T1 oral melanocytic neoplasms was reported to be 38 months (mean) and 18.8 months (median), which was significantly greater than that of dogs with T2 and T3 tumors.…”
mentioning
confidence: 99%
“…Survival times quoted for conventionally treated stage II or III oral CMM (Table 1.) range from 3-to 12 months with metastasis being a significant cause of mortality (Bateman et al, 1994;Freeman et al, 2003;MacEwen et al, 1986;Murphy et al, 2005;Proulx et al, 2003). It is, however, worth noting that not all oral CMMs are clinically aggressive and some early stage canine patients as well as patients with histologically benign lesions can have extended survivals (MacEwen et al, 1986;Smedley et al, 2011).…”
mentioning
confidence: 99%
“…In dogs, radiation therapy can be palliative and prolong life in cases without metastatic disease. 33 However, in most instances, dogs with oral melanoma (stage I-IV) develop metastatic disease and die within 34-110 weeks of diagnosis. The poor outcomes associated with conventional treatments have prompted investigations of alternative treatments for malignant melanoma, including immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate for human patients with disseminated disease is less than 5%; 32 the median survival for dogs with stage III melanoma is 14-16 weeks. [29][30][31]33 Neither single-agent nor combination chemotherapy is effective to treat malignant melanoma. In dogs, radiation therapy can be palliative and prolong life in cases without metastatic disease.…”
Section: Discussionmentioning
confidence: 99%